Strategi Pengembangan Kewirausahaan - Danna Solihin (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2021)
Abstract : Enviromental protection and good management is one of the program mandated in UU No.32 Tahun 2009. Plastic waste to increase every year was a serious problem for the sustainability of natural ecosystems. This study to aim the analyze of Tryada Craft entrepeneurship development strategy in the utilization of plastic waste to be a product selling value. The research method is descriptive analysis through SWOT analysis. The results showed that the availability of raw materials were easily obtained, and that give the entrepreneurs to improve the product quantity, but the lack of available business capital and the use of online media that were not optimal in promotional activities, so made the product not yet interest in society and business training have not been implemented. The emergence of negative public perseptions of waste based products was still a threat to the future development of this business. Therefore, government support for these entrepreneurial activites including providing socialization to the public regarding the safety of using recycled products was an important thing to do. Keywords : SWOT Analysis, Plastic Waste, Environment.